2016
DOI: 10.2147/ijn.s107752
|View full text |Cite
|
Sign up to set email alerts
|

An integrated study on antimicrobial activity and ecotoxicity of quantum dots and quantum dots coated with the antimicrobial peptide indolicidin

Abstract: This study attempts to evaluate the antimicrobial activity and the ecotoxicity of quantum dots (QDs) alone and coated with indolicidin. To meet this objective, we tested the level of antimicrobial activity on Gram-positive and Gram-negative bacteria, and we designed an ecotoxicological battery of test systems and indicators able to detect different effects using a variety of end points. The antibacterial activity was analyzed against Staphylococcus aureus (ATCC 6538), Pseudom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 54 publications
0
30
0
Order By: Relevance
“…The current scientific literature shows apparently contradictory results. For instance, there are studies showing low or no significant toxicity: Blickley et al [34] fed estuarine fish (Fundulus heteroclitus) with one or 10 µg of lecithin-encapsulated CdSe/ZnS QD/day and no significant changes in hepatic total glutathione, lipid peroxidation or oxidative stress was observed, Guo et al [89] exposed zebrafish embryo to graphene QDs (12.5-200 µg/mL for up to 96h and no significant toxicity was observed at concentrations below 50 µg/mL, Galdiero et al [90] showed that QDs functionalized with indolicidin caused low toxicity to D. magna, Lewinski et al [27] studied the trophic transfer of amphiphilic polymer-coated CdSe/ZnS QDs by feeding fish (10 QD contaminated Daphnia) to D. rerio, but no significant adverse effects were noticed. On the other hand, several studies showed that QDs caused different degrees of toxicity in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The current scientific literature shows apparently contradictory results. For instance, there are studies showing low or no significant toxicity: Blickley et al [34] fed estuarine fish (Fundulus heteroclitus) with one or 10 µg of lecithin-encapsulated CdSe/ZnS QD/day and no significant changes in hepatic total glutathione, lipid peroxidation or oxidative stress was observed, Guo et al [89] exposed zebrafish embryo to graphene QDs (12.5-200 µg/mL for up to 96h and no significant toxicity was observed at concentrations below 50 µg/mL, Galdiero et al [90] showed that QDs functionalized with indolicidin caused low toxicity to D. magna, Lewinski et al [27] studied the trophic transfer of amphiphilic polymer-coated CdSe/ZnS QDs by feeding fish (10 QD contaminated Daphnia) to D. rerio, but no significant adverse effects were noticed. On the other hand, several studies showed that QDs caused different degrees of toxicity in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…2). It offers a simple way of evaluating the damage caused by a clastogenic agent by measuring breaks in the DNA chain of animal and plant cells, for example in fish [24][25], mollusks [26][27], earthworms [28][29][30] or arthropods [31][32][33].…”
Section: Methodsmentioning
confidence: 99%
“…Quantum dots (QDs) have received a significant attention in the biomedical field as they possess distinct characteristics over other luminescent materials [33][34][35]. QDs have been widely used for preparing solar cells [36,37], photonic crystal devices including light-emitting diodes [38], and fluorescent probes in cell imaging [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…The typical diameter of a quantum dot is in the range of 1-10 nanometers [43]. Recently, the antibacterial effect of QDs against gram-positive multi-drug resistance (MDR) bacteria such as S. aureus has also been reported [33,34,44]. However, there has been a great deal of concern over the use of QDs in living cells due to their poor biocompatibility, self-agglomeration, and instability in solution.…”
Section: Introductionmentioning
confidence: 99%